Comparison of stability between a modular intraocular lens system and a single‐piece hydrophobic acrylic intraocular lens. Issue 12 (December 2016) - SooHoo, Jeffrey R.; Lane, Stephen S.; Cionni, Robert J.; Berdahl, John P.; Sussman, Glenn R.; Kahook, Malik Y.
Abstract : Purpose : To compare the movement of a modular intraocular lens (IOL) with that of a standard single‐piece hydrophobic acrylic IOL in a human cadaver eye perfusion model. Setting : Department of Ophthalmology, University of Colorado, Aurora, Colorado, USA. Design : Experimental study. Methods : Eight phakic human donor eyes of 4 patients had standard phacoemulsification with lens removal. One of 2 IOLs was then implanted in the capsular bag: a modular IOL (Harmoni) or a standard single‐piece IOL (Acrysof SN60). Each globe was connected to a programmable perfusion pump with an in‐line pressure transducer. Ultrasound biomicroscopy (UBM) was used to evaluate the anterior chamber depth (ACD) in each eye, measuring from the posterior cornea to the anterior surface of the optic at an intraocular pressure (IOP) of 5 mm Hg, 10 mm Hg, 20 mm Hg, and 30 mm Hg. Five consecutive measurements were recorded for all eyes at each pressure, and the results were averaged. Results : There was significantly less movement in eyes with the modular IOL than in eyes with the single‐piece IOL. The mean position of the modular IOL varied from a minimum of 0.03 mm to a maximum of 0.07 mm, and the mean position of the single‐piece IOL varied from a minimum of 0.26 mm to a maximum of 0.87 mm ( P = .002). Conclusions : The modular IOL showed less movement with changes in IOP than a standard single‐piece IOL. Improved IOL stability might allow more accuracy in determining the effective lens position and hence improve the predictability of the refractive target. Financial Disclosure : Proprietary or commercial disclosures are listed after the references.